2012
DOI: 10.1002/smll.201200138
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Interrogation of Bio‐sprayed Cells

Abstract: Bio-sprays can directly form pre-organized cell-bearing structures for applications ranging from engineering functional tissues to the forming of cultures, most useful for modeling disease, to the discovery and development of drugs. Bio-electrosprays and aerodynamically assisted bio-jets, are leading approaches that have been demonstrated as having far-reaching ramifications for regenerative biology and medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…In the case of apoptotic cells, the membrane phospholipid, phosphatidylserine (PS), is translocated from the inner to the outer layer of the plasma membrane, allowing high affinity binding of Annexin V. In the late stages of cell death, the cell membrane loses integrity and becomes leaky to the vital dye PI, thus giving a clear and accurate measurement of the dynamics of cell death. In agreement with our extensive previous studies, no detrimental effects of bio‐electrospraying or cell electrospinning were observed over a 72 h period, in comparison with cell culture controls (abbreviated to “CC”; Figure ).…”
Section: Results Of Two‐way Repeated Measures Anova With Holm–sidak Psupporting
confidence: 92%
See 1 more Smart Citation
“…In the case of apoptotic cells, the membrane phospholipid, phosphatidylserine (PS), is translocated from the inner to the outer layer of the plasma membrane, allowing high affinity binding of Annexin V. In the late stages of cell death, the cell membrane loses integrity and becomes leaky to the vital dye PI, thus giving a clear and accurate measurement of the dynamics of cell death. In agreement with our extensive previous studies, no detrimental effects of bio‐electrospraying or cell electrospinning were observed over a 72 h period, in comparison with cell culture controls (abbreviated to “CC”; Figure ).…”
Section: Results Of Two‐way Repeated Measures Anova With Holm–sidak Psupporting
confidence: 92%
“…Despite the high voltages involved, these cells were surprisingly found to be viable post‐electrospraying/electrospinning; this is due to both these techniques exploring high voltage DC supplies, while applying very low currents (generally in the nA range) . Subsequent work has extended these studies to a wide repertoire of different cell types, both murine and human, immortalized or primary, stem cells, and even whole fertilized embryos from model organisms . Well‐established protocols (such as flow cytometry, genetic/genomic interrogation, and microarray analysis) demonstrated that cells processed using either electrospraying or electrospinning were indistinguishable from controls.…”
Section: Results Of Two‐way Repeated Measures Anova With Holm–sidak Pmentioning
confidence: 99%
“…Moreover, the percentage of viable chondrocytes submitted to certain electrospraying (27G NG and 5 cm NCD) parameters remained high -above 70 %. It should also be emphasized that while other studies have reported higher post-electrosprayed cell viabilities (above 80 -90 %) (Andreu et al, 2012;Braghirolli et al, 2013;Ng et al, 2011;Sahoo et al, 2010;Sampson et al, 2013), it is important to mention that most of these employed substantially bigger NG and smaller NCD, which according to the herein reported data should render high viabilities. Additionally, different electrospraying conditions, viability assay sensitivity and cell susceptibility to damage may also be responsible for the observed difference (Paletta et al, 2011;Sahoo et al, 2010).…”
Section: Discussionmentioning
confidence: 44%
“…[11] These cells were cultured in Dulbecco's modified eagle medium (DMEM) (with 10% fetal calf serum (FCS), 1% non-essential amino acids, 1% sodium pyruvate and 1% penicillin/streptomycin) in tissue culture flasks and incubated at 37 o C with 5% CO 2 . For real time in vivo imaging purposes, the luciferase gene was introduced into the N2A cells by way of a lentiviral system based on the LNT vector type, [12,13] rendering the cells capable of bioluminescence. [13] The tagged cells were suspended in culture medium and incubated at 37 o C with 5% CO 2 until they were required for CE and AABT.…”
Section: Methodsmentioning
confidence: 99%